2022
DOI: 10.1177/01650254221121842
|View full text |Cite
|
Sign up to set email alerts
|

What do I want to be? Predictors of communal occupational aspirations in early to middle childhood

Abstract: Research investigating occupational aspirations in childhood is scarce. In addition, most research on occupational aspirations has focused on increasing the number of women in agentic jobs. In the present work, we investigate factors associated with communal occupational aspirations in two studies with young children (Study 1: 159 children [84 boys, 75 girls], Mage = 5.51 years, SD = 0.37; Study 2: 96 children [48 boys, 48 girls]; Mage = 9.44 years, SD = 1.91). We found gender differences in communal aspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 57 publications
(97 reference statements)
2
13
0
Order By: Relevance
“…This association is in line with Bem's theory of gender schemas: when children incorporate the societal norm that HEED occupations are more suitable for women in their gender schemata, these professions are more interesting for girls than for boys (Liben et al, 2002). This association is in line with the study of Olsen et al (2022) among young children, but not in line with other previous studies among young children, which found no associations between gender-stereotypic attitudes and gender-stereotypic occupational preferences (De Vries et al, 2022;Liben et al, 2002). This illustrates the need for more research on the development of gender-stereotypic interest in HEED careers specifically throughout childhood.…”
Section: Adolescents' Gender-stereotypic Attitudes and Interest In He...supporting
confidence: 86%
See 4 more Smart Citations
“…This association is in line with Bem's theory of gender schemas: when children incorporate the societal norm that HEED occupations are more suitable for women in their gender schemata, these professions are more interesting for girls than for boys (Liben et al, 2002). This association is in line with the study of Olsen et al (2022) among young children, but not in line with other previous studies among young children, which found no associations between gender-stereotypic attitudes and gender-stereotypic occupational preferences (De Vries et al, 2022;Liben et al, 2002). This illustrates the need for more research on the development of gender-stereotypic interest in HEED careers specifically throughout childhood.…”
Section: Adolescents' Gender-stereotypic Attitudes and Interest In He...supporting
confidence: 86%
“…From a young age, children associate and classify certain professions with men and others with women in line with prevailing stereotypes in society (Olsen et al, 2022;Solbes-Canales et al, 2020). Gender stereotypes are 'culturally shared assumptions and expectations about sex differences in abilities, personality traits, activities, and roles' (Weinraub et al, 1984(Weinraub et al, , p. 1493.…”
Section: Adolescents' Gender-stereotypic Attitudes and Interestmentioning
confidence: 99%
See 3 more Smart Citations